Host-microbiota interactions and responses of Metapenaeus ensis infected with decapod iridescent virus 1 - Liao, Minze; Liao, Xuzheng; Long, Xinxin; Zhao, Jichen; He, Zihao; Zhang, Jingyue; Wu, Tingfen; Sun, Chengbo (Frontiers in Microbiology, 2023)
Introduction Decapod iridescent virus 1 (DIV1) has caused severe economic losses in shrimp aquaculture. So far, Researchs on DIV1-infected shrimp have mainly focused on the hemocytes immune response, while studies on the host-intestine microbiota interactions during DIV1 infection have been scarce. Methods This study determined the lethal concentration 50 (LC50) of DIV1 to Metapenaeus ensis, preliminarily determining that M. ensis could serve as a susceptible object for DIV1. The interactions and responses between the immune and intestine microbiota of shrimp under DIV1 infection were also investigated. Results and Discussion DIV1 infection decreases intestine bacterial diversity and alters the composition of intestine microbiota. Specifically, DIV1 infection decreases the abundance of potentially beneficial bacteria (Bacteroidetes, Firmicutes, and Actinobacteria), and significantly increases the abundance of pathogenic bacteria such as Vibrio and Photobacterium, thereby increasing the risk of secondary bacterial infections. The results of PICRUSt functional prediction showed that altered intestine microbiota induces host metabolism disorders, which could be attributed to the bioenergetic and biosynthetic requirements for DIV1 replication in shrimp. The comparative transcriptomic analysis showed that some metabolic pathways related to host immunity were significantly activated following DIV1 infection, including ncRNA processing and metabolic process, Ascorbate and aldarate metabolism, and Arachidonic acid metabolism. M. ensis may against DIV1 infection by enhancing the expression of some immune-related genes, such as Wnt16, heat shock protein 90 (Hsp90) and C-type lectin 3 (Ctl3). Notably, correlation analysis of intestinal microbial variation with host immunity showed that expansion of pathogenic bacteria (Vibrio and Photobacterium) in DIV1 infection could increased the expression of NF-κB inhibitors cactus-like and Toll interacting protein (Tollip), which may limit the TLR-mediated immune response and ultimately lead to further DIV1 infection. Significance and Impact of the Study This study enhances our understanding of the interactions between shrimp immunity and intestinal microbiota. The ultimate goal is to develop novel immune enhancers for shrimp and formulate a safe and effective DIV1 defense strategy.